Cooperative Learning Model of STAD Type To Improve Activity And Achievement of Mathematics Subjects In Subject Number Material - SITI MURNI NUR (International Journal of Management and Education in Human Development, 2023)
Purpose this study to Improve Activity and Achievement of Mathematics Subjects in Subject Number Material with Cooperative Learning Model of STAD. Type Place study is place used in do study for get the desired data. Study This located at SD 92 Kendari Research time is time ongoing study or moment study This took place. Study This held in month February semester even odd Year 2022. Subject study is students Class VI 2 SD 92 Kendari. Based on existing deficiencies and achievements Study students in cycle I who have not fulfil standard success, then study This continued in cycle II. Research results show that activity learning has in accordance with hope. Weaknesses in cycle I have overcome in cycles II so all student has reach standard completeness learn. Teacher activity in learning Cooperative model in STAD learning Mathematics obtained at the meeting First teacher activity with use learning Cooperative model in STAD learning with score of 65 or on, category enough and at the meeting second obtained score of 70 or category good and average overall obtained 67.5 or category enough. Furthermore, activity student with use learning Cooperative model in STAD learning Mathematics meeting I was at a score of 53.93 or category sufficient and meeting II obtained 64.48 or category enough and overall average obtained 59.21 or category enough. Study results student obtained the average value of achievement Study Mathematics student is 65.58. Complete students’ study amya is 20 people or 64.67% and students who do not complete results learn was 14 people or 35.32%. those results show that on cycle First in a manner classic student Not yet complete learn. Teacher activity in cycle II at the meeting First teacher activity with use learning with use learning Cooperative model in STAD learning Mathematics obtained score of 80 or category well and at the meeting second obtained score of 90 or category very good and average overall obtained 85 or category ok. At the first meeting it was at a score of 76.98 or category well and. meeting H obtained 88.89% or category very good and average overall obtained 82.14 or category ok. Study results students in cycle II obtained the average value of achievement Study student is 70.29 and completeness Study reached 94.11% or there are 32 students of 34 students Already done, learn. those results show that on cycle First in a manner classic student complete learn, because students who get value > 70 only of 94.11% yield the completeness Study student has achieved because that got value > 70 more big of 85% match from percentage the desired completeness. Based on matter the so can said that learning model STAD cooperative model can be give very good impact to activities of teachers, students and and results Study Mathematics students in Class VI SD 92 Kendari.